Entanglement Detection: A Scoping Review - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan; Mohamed Ridza Wahiddin (SEMARAK ILMU PUBLISHING, 2024)
Indexed by Scopus/MyCite